Strategies of peace culture in childhood education under the educators 'views (Research, Society and Development, 2021)
Promoting the Culture of Peace is one of the essential components of child health and its approach to early childhood education. From the social challenges observed in teaching, research and university extension activities, the objective of knowing the perception of educators about strategies for a culture of peace in early childhood education emerged. Qualitative study, carried out in a Municipal Center for Early Childhood Education, in an area of ​​social vulnerability in the city of Maceió-AL, from December 2019 to March 2020, with nine professionals in early childhood education, using Group technologies Focal for the evaluation of aspects related to the Culture of Peace. From the meetings, it was evident that the speeches converged into three categories: the concept of the culture of peace, working with the culture of peace at school and the construction of culture strategies of peace. The scarcity of studies and the difficulty in understanding the theme, as well as the importance of integrating education and the promotion of a culture of peace, were aspects that resulted in the suggestion of building a board game to support conflict resolution in a non- violent. The study pointed out contributions to the promotion of the Culture of Peace and playful strategies for the context of Early Childhood Education, as well as the need for further research to explore the theme.